Online crisis management and its informational treatment in areas of knowledge and communication in Spain in the period of 2008-2018 - Smolak Lozano, Emilia (2020)
Due to the rise of Social Media, the management of online reputation crises becomes increasingly important in the agenda setting of the media, in the teaching of the profession of communication management, as well as its practice. The peculiarity of communication flows in the digital ecosystem, the speed, scope and interactivity of social networks means that crises managed in the digital environment are characterized by great impact and difficulty in containing unwanted effects. They require a detailed analysis, good preparation and contingency plans, which in turn must be reflected in the media, professional and academic analyzes framed as failures, good practices or recommendations based on the theory, praxis and analysis of the facts. A study has been devised to cover three areas of information on online crisis cases: “journalistic”, “scientific” and “professional”. 10 years of publications in the press, academia and specialized platforms in Spain on online crisis management have been analyzed, collecting data on the treatment and coverage of these case studies. The results reflect a limited interest in these three information areas in regards to